Role of Transient Receptor Potential Canonical Channel 6 (TRPC6) in Diabetic Kidney Disease by Regulating Podocyte Actin Cytoskeleton Rearrangement - Qian Wang; Xuefei Tian; Yuyang Wang; Yan Wang; Jialin Li; Tingting Zhao; Ping Li (Journal of Diabetes Research)
Podocyte injury is an important pathogenesis step causing proteinuric kidney diseases such as diabetic kidney disease (DKD). Actin cytoskeleton rearrangement in podocyte induced by multiple pathogenic factors is believed to be the key process resulting in glomerular injury. Many studies have recently shown that transient receptor potential canonical channel 6 (TRPC6) in podocyte plays a critical role in the development and progression of proteinuric kidney disease by regulating its actin cytoskeleton rearrangement. This review is aimed at summarizing the role of TRPC6 on DKD by regulating the podocyte actin cytoskeleton rearrangement, thereby help further broaden our views and understanding on the mechanism of DKD and provide a theoretic basis for exploring new therapeutic targets for DKD patients.